3‐Rhoda‐1, 2‐diazacyclopentanes: A Series of Novel Metallacycle Complexes Derived From CN Functionalization of Ethylene. Issue 41 (28th August 2014) - Drover, Marcus W.; Beh, Daniel W.; Kennepohl, Pierre; Love, Jennifer A.
Abstract Rh‐containing metallacycles, [(TPA)RhIII(κ2‐(C, N)‐CH2CH2(NR)2‐]Cl; TPA=N, N, N, N‐tris(2‐pyridylmethyl)amine have been accessed through treatment of the RhI ethylene complex, [(TPA)Rh(η2‐CH2CH2)]Cl ([1]Cl) with substituted diazenes. We show this methodology to be tolerant of electron‐deficient azo compounds including azo diesters (RCO2NNCO2R; R=Et [3]Cl, R=iPr [4]Cl, R=tBu [5]Cl, and R=Bn [6]Cl) and a cyclic azo diamide: 4‐phenyl‐1, 2, 4‐triazole‐3, 5‐dione (PTAD), [7]Cl. The latter complex features two ortho‐fused ring systems and constitutes the first 3‐rhoda‐1, 2‐diazabicyclo[3.3.0]octane. Preliminary evidence suggests that these complexes result from N–N coordination followed by insertion of ethylene into a [Rh]N bond. In terms of reactivity, [3]Cl and [4]Cl successfully undergo ring‐opening using p‐toluenesulfonic acid, affording the Rh chlorides, [(TPA)RhIII(Cl)(κ1‐(C)‐CH2CH2(NCO2R)(NHCO2R)]OTs; [13]OTs and [14]OTs. Deprotection of [5]Cl using trifluoroacetic acid was also found to give an ethyl substituted, end‐on coordinated diazene [(TPA)RhIII(κ2‐(C, N)‐CH2CH2(NH)2‐]+ [16]Cl, a hitherto unreported motif. Treatment of [16]Cl with acetyl chloride resulted in the bisacetylated adduct [(TPA)RhIII(κ2‐(C, N)‐CH2CH2(NAc)2‐]+, [17]Cl. Treatment of [1]Cl with AcNNAc did not give the RhN insertion product, but instead the N, O‐chelated complex [(TPA)RhI(κ2‐(O, N)‐CH3(CO)(NH)(NC(CH3)(OCHCH2))]Cl [23]Cl, presumably through insertion of ethylene into a [Rh]O bond.